Muḥammad Iqbāl in the eyes of Arabic Litterateurs - Anjum, Salma; Bibi, Nazia (Journal of Islamic and Religious Studies, 2016)
Iqbāl is known as a revolutionary poet, and Islamic intellectual, a religious reformer, pioneer of Islamic awareness and a great leader of the Muslims of the sub-continent. He was introduced to the Arab world during the early part of 20th century and became popular after the translations of his work into Arabic. Scholars, thinkers, writers, and politicians of Arabia were very much influenced by his literary works. A number of books were written on him. Other scholars and Muslim thinkers study his works with keen interest even in the modern times. Iqbāl was paid rich tributes by Arab writers and thinkers for his unique wealth of literary works. In this article we present the views of Arabian writers about his literary status.